Inflammation and anemia in simple febrile seizures and complex febrile seizures - Polat, Ipek; Karaoglu, Pakize; Ayanoglu, Muge; Cirali, Ceren; Bayram, Erhan; Yis, Uluc; Hiz, Semra (Annals of Medical Research, 2021)
Aim: This is a unique study that aimed to determine anemia and inflammatory status in simple febrile seizure vs complex febrile seizure patients. Neutrophil/lymphocyte ratio and platelet/lymphocyte ratio are positively correlated with inflammatory markers including TNF alpha and IL-6. They are practical, inexpensive, and valuable tools for evaluating inflammation. Materials and Methods: Patients presenting with first febrile seizures were enrolled retrospectively. We investigated hemoglobin, hematocrit, mean corpuscular volume, mean corpuscular hemoglobin concentration and red blood cell distribution width values and white blood cell count, neutrophil, lymphocyte count, neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, and mean platelet volume, C - reactive protein. Results: Our study showed that higher neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, and lower mean platelet volume values in complex febrile seizure cases than simple febrile seizure cases. We determined cut-off values for neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, and mean platelet volume of 2.5, 10523.3, and 7.3 respectively. Conclusion: High neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, and low mean platelet volume values can help distinguish simple febrile seizure and complex febrile seizure patients and predict the clinic. The optimal cut-off values that we determined may guide clinicians.